2014
DOI: 10.1097/fbp.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an α5GABAA inverse agonist on MK-801-induced learning deficits in an incremental repeated acquisition task

Abstract: N -methyl-D-aspartate receptors (NMDARs) are essential for several kinds of synaptic plasticity and play a critical role in learning and memory. Deficits in NMDAR functioning may be partially responsible for the learning and memory deficits associated with aging and numerous diseases. Administration of MK-801, a noncompetitive NMDAR antagonist, is commonly used as a preclinical model of NMDAR dysfunction. The objective of this study was to assess the effects of α5GABAA receptor inhibition on learning deficits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The doses of L-655,708 (0.5-1.0 mg/kg) that we used are similar to the doses that have previously been found to improve performance in the Morris water maze [35]. Similarly, others found that L-655,708, at the dose range used in the current study, reversed deficits in social interaction caused by chronic stress [49] and learning deficits following administration of the NMDA receptor antagonist MK-801 [50]. Although we cannot rule out the possibility that a higher dose L-655,708 could have affected 5CSRTT performance, it seems unlikely.…”
Section: Role Of Gaba a Receptors In Attentionsupporting
confidence: 79%
“…The doses of L-655,708 (0.5-1.0 mg/kg) that we used are similar to the doses that have previously been found to improve performance in the Morris water maze [35]. Similarly, others found that L-655,708, at the dose range used in the current study, reversed deficits in social interaction caused by chronic stress [49] and learning deficits following administration of the NMDA receptor antagonist MK-801 [50]. Although we cannot rule out the possibility that a higher dose L-655,708 could have affected 5CSRTT performance, it seems unlikely.…”
Section: Role Of Gaba a Receptors In Attentionsupporting
confidence: 79%
“…Initially, it was proposed that selective GABA A -α5 NAMs may be beneficial for Alzheimer’s Disease and mild cognitive impairment 16 . Since then, further preclinical studies suggest that GABA A -α5 NAMs may attenuate cognitive impairment associated with Down syndrome (DS) 17 , 18 , cognitive impairment associated with schizophrenia (CIAS) as shown by improvements in preclinical models of NMDA dysfunction 19 21 and cognitive impairment after anesthesia 22 . In addition, studies in mice and rats have shown that after ischemic stroke there is increased GABA A -α5 mediated tonic inhibition in the peri-infarct area and that reduction of GABA A -α5 activity enhances functional recovery after stroke 23 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides phencyclidine, dizocilpine (MK-801) is another experimentally widely used NMDA receptor antagonist, and MK-801-induced cognitive impairments have been validated as a rodent model related to human cognitive deficits associated with dementia (Van der Staay et al, 2011) and schizophrenia (Adell et al, 2012; Andine et al, 1999). Although the MK-801-induced memory deficit model has been assessed as the second most commonly (after scopolamine) used deficit model in preclinical cognition research (Van der Staay et al, 2011), the published results of testing the selective α 5 GABA A receptor negative modulators in animals treated with MK-801 are limited to only one study, using the incremental repeated acquisition task which allows for the assessment of effects on learning at various levels of task-difficulty (Povroznik et al, 2014). Such data are expected to be of special relevance in the pursuit of novel therapies for cognitive aspects of neuropsychiatric disorders, beginning with the premise that α 5 GABA A receptors located at the base of dendritic spines of pyramidal cells in the hippocampus and neocortex are strategically located to modulate excitatory glutamatergic input that arrives at the spines of these cells (Rudolph and Möhler, 2014).…”
Section: Introductionmentioning
confidence: 99%